Weaning and 18-month weights of Boran, East African Shorthorn Zebu and Sahiwal breeds or crosses in Kenya - Mwandotto, B.A.J.; Carles, A.B.; Cartwright, T.C. (1988)
Comparative evaluation of some cattle breeds and their crosses were done to provide a basis for recommendations on the direction of breeding and management of cattle for enhanced productivity in semi-arid and arid areas of Kenya. Data from 1055 calves of Small East African Shorthorn Zebu (Z), Boran (B), Sahiwal (S), B x Z, S x Z, Friesian (S), F x B and F x S breed types were analysed to identify and quantify factors affecting weaning and 18-month weights. Breed type, sex, year, season and birth month within season, weaning age, total rainfall and age of dam affected weaning weight (P